National Semiconductor Melaka Success In Supporting The Corporation Key Strategy Of Lowest Cost Producer By Delivering Reduced Manufacturing Cost Per K Units Even In A Slow Business Situation - Leong, Oh Eng (2004)
This project will dwell generally into the concept of world class manufacturing and what are the center of excellence required in order to support and deliver the required results for the 8 key targets and thus for NSEM and in particular for NSC to become the lowest cost producer.